What Religion Affords Grassroots NGOs: Frames, Networks, Modes of Action - Schnable, Allison (Journal for the scientific study of religion, 2016)
The international relief and development sector has swelled in the last two decades thanks to American grassroots NGOs: groups that rely on volunteer labor and individual contributions, often on budgets of less than $25,000 a year. Most of these organizations reject the label of faith-based organization, yet they find the symbolic and material resources of religion indispensable. Religion affords these NGOs three kinds of resources to meet their distinct organizational needs. First, it provides frames, or ways of thinking and speaking about relief and development work that imbue it with legitimacy. Next, religion offers networks that provide money, volunteers, and entrée into aid-receiving communities. Finally, religion affords familiar modes of action that link the NGO, supporters, and local aid recipients. I support these claims with LDA topic modeling (a computerized method of text analysis), content analysis of websites, and in-depth interviews with 43 informants.